Pengelolaan Keuangan Yang Efektif Sebagai Kunci Keberhasilan Realisasi Anggaran Dana Desa Cangkring, Kecamatan Jenggawah Tahun 2024 - Amanda Dewi Arian; Anggun Aurellia Rahman; Revanda Marissa; Rafa Aditya Nur Rohmanita; Prillinaya Yudhistira; Oryza Ardhiarisca (MUARA EKONOMI : Jurnal Ilmiah Ilmu Ekonomi, Manajemen & Bisnis, 2025)
This study aims to analyze how finances are managed regarding the use of the 2024 Village Fund budget in Cangkring Village, Jenggawah District, Jember Regency. The focus of this study is to analyze the extent to which budget realization has been in accordance with the activity plans stated in the RKPDes and APBDes, because there are still several problems in adjusting between the plan and the actual use of the budget, such as delays in disbursement of funds caused by delays in the preparation of the plan. This study uses a qualitative approach with descriptive techniques. The main instrument of the study is direct research with documentation and interviews through competent people, namely the village treasurer as the head of finance, who was selected using a purposive sampling technique. The results of the study concluded that the process of managing Village Funds in Cangkring Village has been carried out in accordance with the stages stipulated in the Regulation of the Minister of Home Affairs Number 20 of 2018 concerning Village Financial Management, which includes planning, implementation, administration, reporting, and village financial accountability, and is carried out in a transparent, accountable, and participatory manner. Overall, the management and disbursement of the 2024 Village Fund in Cangkring Village has been quite effective and efficient, but still requires improvements in capacity, speed of fund disbursement, and optimization of the village financial information system